Structure of the prosthetic group of Klebsiella aerogenes citrate (pro-3S)-lyase. - Robinson, J B (1976)
The prosthetic group of citrate (pro-3S)-lyase [citrate oxaloacetate-lyase (pro-3S-CH2COO- leads to acetate); EC 4.1.3.6] from Klebsiella aerogenes was obtained by mild alkaline hydrolysis of the enzyme and purified by DEAE-cellulose chromatography. Several chemical and enzymatic degradation products of the compound have been isolated, and analyses of these have shown the structure of the prosthetic group to be 3'(or 2') leads to 1 inch-(5 inches-phosphoribosyl) dephosphocoenzyme A. Proof as to the exact linkage between the two ribose moieties and the anomeric configuration of the glycosidic bonds has not yet been obtained. A similar analysis was obtained for a product isolated after Pronase digestion of the enzyme (without alkaline hydrolysis). The isolated prosthetic group also can serve as a substrate for a crude preparation of acetate:-SH-(acyl carrier protein) enzyme ligase (AMP) from K. aerogenes, pure pig heart citrate (si)-synthase (EC 4.1.3.7), and pure rat liver ATP citrate (pro-3S)-lyase (EC4.1.3.8). This compound is the first shown to substitute for coenzyme A in the latter reaction.